DEVELOPMENT OF POP UP BOOK MEDIA LEARNING GEOGRAPHY IN PRINGSEWU SENIOR HIGH SCHOOL - Pargito Pargito; Zulkarnain Zulkarnain; Dedy Miswar; Nani Suwarni; Eni Ayu Lestari (Journal Learning Geography, 2021)
The purpose of this study was to develop Pop Up Book learning media in learning geography in high school. The research method used is Research and Development (RD) research with Borg Gall development procedures with seven steps that have been modified by researchers, namely: Research and information, Planning, Developing Preliminary From of Product, Preliminary Field Testing, Main Product Revison, Main Field Product Revision Testing and Operations. The results of this study to assess the feasibility of instructional media materials experts at 81 , 76 %, 93.3% of media experts, linguists 95%. Validation in a broader context teachers get a score of 93.18% and students get a score of 92.67% presentation results exceed 80% in the learning media category feasible to use. In the T-test calculation, the value of sig (2-tailed) is 0,000, which means the value of 0,000 is smaller than 0.005. Thus there is the influence of understanding the concept after using Pop Up Book learning media and before using.Tujuan penelitian ini untuk mengembangkan media pembelajaran Pop Up Book dalam pembelajaran geografi di SMA. Metode penelitian yang digunakan adalah penelitian Research and Development (RD) dengan prosedur pengembangan Borg Gall dengan tujuh langkah yang telah dimodifikasi oleh peneliti yaitu: Research and information, Planning, Develop Preliminary From of Product, Preliminary Field Testing, Main Product Revison, Main Field Testing dan Operational Product Revision. Hasil penelitian ini menilai kelayakan media pembelajaran dari ahli materi sebesar 81,76%, ahli media 93,3%, ahli bahasa 95%. Validasi dalam konteks yang lebih luas guru mendapatkan skor 93,18% dan siswa mendapatkan skor 92,67% hasil presentasi melebihi 80% di kategorigan media pembelajaran layak digunakan. Pada perhitungan T-test didapakan nilai sig (2-tailed) sebesar 0,000 yang artinya nilai 0,000 lebih kecil dari pada 0,005. Dengan demikian terdapat pengaruh pemahaman konsep setelah menggunakan media pembelajaran Pop Up Book dan sebelum menggunakan.